Evolution of the plasma environment of comet 67P from spacecraft potential measurements by the Rosetta Langmuir probe instrument. Issue 23 (11th December 2015) - Odelstad, E.; Eriksson, A. I.; Edberg, N. J. T.; Johansson, F.; Vigren, E.; André, M.; Tzou, C.‐Y.; Carr, C.; Cupido, E.
Abstract: We study the evolution of the plasma environment of comet 67P using measurements of the spacecraft potential from early September 2014 (heliocentric distance 3.5 AU) to late March 2015 (2.1 AU) obtained by the Langmuir probe instrument. The low collision rate keeps the electron temperature high (∼5 eV), resulting in a negative spacecraft potential whose magnitude depends on the electron density. This potential is more negative in the northern (summer) hemisphere, particularly over sunlit parts of the neck region on the nucleus, consistent with neutral gas measurements by the Cometary Pressure Sensor of the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis. Assuming constant electron temperature, the spacecraft potential traces the electron density. This increases as the comet approaches the Sun, most clearly in the southern hemisphere by a factor possibly as high as 20–44 between September 2014 and January 2015. The northern hemisphere plasma density increase stays around or below a factor of 8–12, consistent with seasonal insolation change. Key Points: Plasma density, deduced from spacecraft potential, traces neutral density, implying local ionization We determine the plasma density increase due to decreased heliocentric distance and seasonal effects Low collision rate keeps the electron temperature high (∼5 eV), giving a negative spacecraft potential